The Significance of Positron Emission and Computerized Tomography with Fluorodeoxyglucose in the Post-Therapeutic Evaluation of Patients with Uterine Carcinoma - Jelić, Ivona; Isaković, Vuk; Jovanović, Slađan; Odalović, Strahinja (Medicinski podmladak, 2019)
Introduction: The positron emission tomography with computerized tomography is a valuable machine in identifying tumors - it can determine the exact size and position of the cancer, as well as the effect of therapy. The duality of this technique provides information on the metabolic activities of the neoplasm and a precise anatomical location.Aim: The aim of this study was be to determine the diagnostic performance of FDG PET/CT in detection of recurrent disease and to determine the stage of the disease after the application of therapy in patients with cervical carcinoma.Material and methods: In this study, a total of 38 patients were included, in whom FDG PET/CT was made from 2010 to 2017. The diagnostic contribution of FDG PET/CT in the detection and identification of the recurrence of cervical cancer was determined by calculating the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV).Results: The sensitivity, specificity, PPV, NPV and diagnostic accuracy of FDG PET/CT in the detection of local and distant relapses of cervical carcinoma were 90%, 75%, 93.1%, 66.7% and 86.8%, respectively. There were 27 true positive, 2 false positive, 6 true negative and 3 false negative findings.Conclusion: The FDG PET/CT has proven to be a very sensitive method in the detection of secondary deposits of cervical cancer. Of particular importance is in the evaluation of the patient with this diagnosis. The metabolic activity of lesions (SUV max) did not have an impact on the therapeutic response. Key words: FDG PET/CT, cervical cancer, evaluation.
Keywords: FDG PET/CT; evaluation; cervical cancer